Development and Validation of the Hospital for Special Surgery Anterior Cruciate Ligament Reconstruction Preoperative Expectations Survey. Issue 12 (15th June 2020) - Kahlenberg, Cynthia A.; Mehta, Nabil; Fabricant, Peter D.; Zhang, David T.; Nguyen, Joseph; Williams, Riley J.; Allen, Answorth A.; Nwachukwu, Benedict U.
Abstract : Introduction: Understanding and meeting the patients' preoperative expectations for anterior cruciate ligament (ACL) reconstruction (ACLR) is critical for achieving successful patient-centered outcomes. There is currently no standardized method to assess preoperative expectations of ACLR based on the patient-derived methods. The purpose of this study was to develop and test a patient-derived patient expectations survey specific to primary ACLR. We hypothesized that a valid and reliable patient-derived survey could be developed to measure these expectations and that patients would have diverse expectations before surgery. Methods: The Hospital for Special Surgery ACL-expectation score was developed through a four-phase iterative process that included item generation and pilot survey development, item reduction, survey readability, and survey validation. Seventy-two patients were involved in the development phase, and 80 patients were included in the validation phase. Discriminant validity testing was performed regarding age and sex. Cronbach alpha was calculated to assess the internal consistency of responses in the survey. Results: The final survey instrument consisted of 10 questions scored on a visual analog scale from 1 to 10, for a maximum score of 50 points. No statistically significant differences were observed in the score between men and women ( P = 0.517) nor between age quartiles ( P = 0.807). No statistically significant difference was observed in the scores when each sex was stratified by age quartile ( P = 0.275 for men, P = 0.878 for women). Cronbach alpha for all items was 0.745, indicating excellent internal consistency. The intraclass correlation coefficient for test-retest reliability was 0.774, indicating a strong correlation. Conclusion: The Hospital for Special Surgery ACL-expectations score is a patient-derived, tested and reliable preoperative expectations measure with excellent psychometrics for active adults undergoing ACLR. We suggest future clinical studies in ACLR to incorporate this tool as a preoperative measure of patient expectations.